Managing Attrition: A Case Study - Aneet,; Kumar, Prem (Gyan Management Journal, 2008)
To be a world-class textile organi_zation by producing a diverse range of products for the Global Textile Market. Lotus seeks to achieve customer delight through excellence in manufacturing and customer service based on a combination of state-of-the-art technology and human resources. Lotus is committed to being a responsible corporate citizen.,, Back in 1993, when the Chairman Of Lotus Group of Companies met Mr Wang of KBL of South Korea, they started discussing the possibility of launching a manufacturing unit for Gassed Mercerized Yarn or GMY in India. GMY is a specialized yarn, produced by means of a highly technical manufacturing process. t is used in manufacturing world-class quality socks, t-shirts and knitted fabric for sports and casual wear. Garment manufacturers in India used to import GMY from Japan, Korea and Europe.
Keywords: Managing Attrition; Global Textile Market